The world is not for sale : farmers against junk food / Jose Bove ; Francois Dufour ; Gilles Luneau. - Bove, Jose (Verso, 2001)
Jose Bove, a French farmer, has become a leading figure in the global anti-capitalist protests. This book tells his story and examines the issues behind two of his WTO protests in Seattle. This translation originally published: 2001